Effectiveness of 5-aminolevulinic Acid-mediated Photodynamic Therapy Combined With Curcumin - Siu Kan Law (Mazandaran University of Medical Sciences, 2023)
5-Aminolevulinic acid (5-ALA) is the mitochondria metabolite produced from glycine and succinyl-CoA, which is converted to protoporphyrin IX (PpIX) by the conjugation of eight itself molecules forming the "heme" group in the porphyrin ring (Figure 1) [1]. The PpIX is used as a photosensitizer (PS) with an absorption wavelength of 410 nm, and 5-ALA acts as a precursor or prodrug for PpIX in photodynamic therapy (PDT). Exogenous administration of excessive amounts of 5-ALA increases the production of PpIX during heme biosynthesis. It is eliminated after 24-48 h with a lower risk of long-term photosensitivity [2]. However, ALA/PDT has several disadvantages. For instance, the concentration of ALA is affected by its absorption and pharmacokinetics that do not fully cover the treatment area [3-5]. It also limits the depth of tumor penetration and causes pain [6].